Google Classroom Learning Media Acceptance and Use Analysis Using Technology Acceptance Model (TAM) - Indyah Hartami Santi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Google Classroom learning media in distance learning classes becomes a medium worth considering. The purpose of this study was to find out the level of admission of students in using google classroom learning media. The approach method is carried out by quantitative method by spreading the questionnaire to students and the results of this data collection are calculated using SPSS. The analysis model used is the Technology Acceptance Model. From calculations and analysis obtained the result that the relationship between ease of use of intentions and interface design relationship to usability is rejected. While the result of the relationship of usability to intention, the relationship between intention with the use of technology, the relationship between interface design with ease, the relationship of experience to ease and the relationship of ease to usefulness received